Cognitive Orientation to daily Occupational Performance (CO-OP) for Older Adults After a Hip Fracture: A Pilot Study. - Appleton, Esther; Maeir, Talia; Kaufman, Yakir; Karni, Sharon; Gilboa, Yafit (American Journal of Occupational Therapy)
Importance: In-home therapy provides the opportunity for rehabilitation intervention to be completed in the context of the patient's natural environment. However, most studies have focused on the effects of physical exercise, leaving a gap in understanding the effectiveness of a more task-oriented intervention that addresses individual preferences. Objective: To assess the feasibility and preliminary efficacy of the Cognitive Orientation to daily Occupational PerformanceTM (CO-OP) approach, delivered at home with older adults after a hip fracture to improve functional outcomes. Design: Single-arm quasi-experimental design. Setting: Patients' home. Participants: Nine participants (age ≥60 yr) being discharged home from an inpatient rehabilitation ward in a geriatric hospital in a central city in Israel. Intervention: Up to 10 1-hr weekly face-to-face sessions in using the CO-OP approach. Outcomes and Measures: The Canadian Occupational Performance Measure was used to measure performance and satisfaction with the patients' level of participation in daily functioning. Results: A 30% recruitment rate, an 81% retention rate, were observed, with 88% of the participants expressing high to very high overall satisfaction with the intervention. Friedman test results indicated statistically significant improvements in occupational performance and satisfaction on trained and untrained goals (p <.01). Conclusions and Relevance: The findings suggest that a home-based CO-OP intervention is feasible and potentially beneficial for older adults who are returning home after a hip fracture. What This Article Adds: This study shows that a task-oriented intervention can be effective in helping older adults return home successfully after a hip fracture. A task-oriented, home-based Cognitive Orientation to Daily Occupational PerformanceTM (CO-OP) intervention can be effective in helping older adults return home successfully after a hip fracture.